METODE PENENTUAN RUGI-RUGI HISTERESIS PADA PENGATURAN MOTOR INDUKSI BERBASIS VECTOR CONTROL - Novrian Eka Sandhi; Era Purwanto; Dedid Cahya Happyanto; Ridwan W.K.; Handri Toar (JURNAL INTEGRASI, 2020)
Compared to direct current (DC) motors, the three-phase induction motors have several advantages such as: big torque, low maintenance cost, and rugged. For those reasons, induction motors are dependable as the prime mover in industrial and transportation sectors. In order to increase the performance of induction motors, a vector control based driving method had been deleveloped to operate the induction motors in various level of speed. Some manufacturers begin to use induction motors as the mover of 2 or 4-wheeled electric vehicles in city/urban transportation. Due to restricted capacity of battery as the power source, many researches on vector control are now focussed on advancing the driving scheme which in turn increasing mileage and lifetime of induction motors. One factor which supports that purpose is the evaluation of losses occurred during induction motor operation. During low speed operation, hysteresis loss as a consequence of stator core magnetization phenomenon takes a major part of overall losses. This research proposed a simple and applicable design of hysteresis loss determination on induction motor controlled by vector control scheme. The simulation using particular induction motor as a sample found that the iron loss PFE ranged between 2,55 x 10-8 to 1,09 x 103 Watt, the hysteresis loss Ph ranged between 2,07 x 10-8 to 5,15 x 102 Watt, and the hysteresis loss to iron loss rate ranged between 47,09 % to 81,18 %.